2012
DOI: 10.1007/s00125-011-2429-5
|View full text |Cite
|
Sign up to set email alerts
|

Insulin glargine and risk of cancer: a cohort study in the French National Healthcare Insurance Database

Abstract: Aims/hypothesisUsing the Echantillon Généraliste de Bénéficiaires: random 1/97 permanent sample of the French national healthcare insurance system database (EGB), we investigated whether, as previously suspected, the risk of cancer in insulin glargine (A21Gly,B31Arg,B32Arg human insulin) users is higher than in human insulin users. The investigation period was from 1 January 2003 to 30 June 2010.MethodsWe used Cox proportional hazards time-dependent models that were stratified on propensity score quartiles for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 45 publications
2
56
1
2
Order By: Relevance
“…The first study to suggest a potential risk of glargine versus human insulin found an OR of 1.31 (95% CI 1.20-1.42) for breast cancer in high-dose users only (.50 UI) while only controlling for a limited number of factors (3). A study from the (18). The large mortality deficit between the two populations might reflect a lack of comparability between populations.…”
Section: Discussionmentioning
confidence: 99%
“…The first study to suggest a potential risk of glargine versus human insulin found an OR of 1.31 (95% CI 1.20-1.42) for breast cancer in high-dose users only (.50 UI) while only controlling for a limited number of factors (3). A study from the (18). The large mortality deficit between the two populations might reflect a lack of comparability between populations.…”
Section: Discussionmentioning
confidence: 99%
“…The EGB has already been used for pharmacoepidemiologic research (Blin, Lassalle et al 2012;Dupouy, Fournier et al 2013;Gallini, Andrieu et al 2013). It includes salaried workers, agricultural workers and farmers, self-employed individuals, retired persons and patients with universal coverage (low income beneficiaries) (Tuppin, de Roquefeuil et al 2010).…”
Section: Settings and Populationmentioning
confidence: 99%
“…There were four Taiwanese studies from the same cohort (15,34,43,44), and hence, only one report was included in the main analysis (34). There were three studies that compared the association between insulin glargine (as compared with nonglargine insulin) and the risk of cancer, and these were excluded from analysis (45)(46)(47).…”
Section: Resultsmentioning
confidence: 99%